A Suggested Improvement to The Plant Recovery Formula: A Case Study for Elazig Ferrochrome Plant - Ankara, Huseyin (Asian Journal of Chemistry, 2010)
The plant recovery is widely used for an assessment of plant performance in mineral and metal processing plants. It has been formulized as a uniform function in the form of a ratio of output to input. In this study, plant recovery formula in an exponential form was developed based on exponential distribution. First of all, plant recovery in the exponential form was shown with the establishment of probability density functions, based on the parameters of assays in feed, concentrate (or mineral) and tailing (or slag) depending on assay in feed. Characteristic parameters and probability density functions of exponential distribution were adapted for the plant recovery formula. The plant recovery in the exponential form was determined by using the data over a 1-month period in Elazig ferrochrome plant-B in Turkey. Only the lowest assays in feed were picked from the data obtained over a 11 month period and re-analyzed to determine the changes existing the recovery. Significant difference was not observed with both calculations performed the suggested recovery formula. As a result of this study, it is shown that plant recovery based on the exponential distribution can be used effectively to determine whether under control of the process or not.